Influence of the world`s most challenging mountain ultra-marathon on energy cost and running mechanics - Vernillo, G.; Savoldelli, A.; Zignoli, A.; Trabucchi, P.; Pellegrini, B.; Millet, G. P.; Schena, F. (European Journal of Applied Physiology, 2014)
Purpose To examine the effects of the world`s most challenging mountain ultra-marathon (Tor des Géants® 2012) on the energy cost of three types of locomotion (cycling, level and uphill running) and running kinematics. Methods Before (pre-) and immediately after (post-) the competition, a group of ten male experienced ultra-marathon runners performed in random order three submaximal 4-min exercise trials: cycling at a power of 1.5 W/kg body mass; level running at 9 km/h and uphill running at 6 km/h at an inclination of +15 % on a motorized treadmill. Two video cameras recorded running mechanics at different sampling rates. Results Between pre- and post-, the uphill-running energy cost decreased by 13.8 % (P = 0.004); no change was noted in the energy cost of level running or cycling (NS). There was an increase in contact time (+10.3 %, P = 0.019) and duty factor (+8.1 %, P = 0.001) and a decrease in swing time (-6.4 %, P = 0.008) in the uphill-running condition. Conclusion After this extreme mountain ultra-marathon, the subjects modified only their uphill-running patterns for a more economical step mechanics.